2011
DOI: 10.1016/j.joi.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The first Italian research assessment exercise: A bibliometric perspective

Abstract: a b s t r a c tIn December 2003, seventeen years after the first UK research assessment exercise, Italy started up its first-ever national research evaluation, with the aim to evaluate, using the peer review method, the excellence of the national research production. The evaluation involved 20 disciplinary areas, 102 research structures, 18,500 research products and 6661 peer reviewers (1465 from abroad); it had a direct cost of 3.55 millions Euros and a time length spanning over 18 months. The introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 38 publications
(51 reference statements)
0
54
0
5
Order By: Relevance
“…Although some studies suggest that indicator-based systems are cheaper than peer review assessment (Franceschet and Costantini, 2011), we found no published material detailing the costs of a metrics-based system. To fill this gap, we interviewed managers and experts in Norway and Sweden where metrics-based systems are used to allocate part of their research budgets.…”
Section: The Cost Of Metrics-based Systemsmentioning
confidence: 90%
“…Although some studies suggest that indicator-based systems are cheaper than peer review assessment (Franceschet and Costantini, 2011), we found no published material detailing the costs of a metrics-based system. To fill this gap, we interviewed managers and experts in Norway and Sweden where metrics-based systems are used to allocate part of their research budgets.…”
Section: The Cost Of Metrics-based Systemsmentioning
confidence: 90%
“…Essa revisão é necessária, sobretudo, para que se evite a cristalização de parâmetros e critérios e para que se discutam criticamente as consequências que produzem, evitando distorções 6,7 . A avaliação tem um papel indutor importante no desenvolvimento da área, pois os critérios utilizados orientam os caminhos para a organização dos programas e apontam tendências.…”
Section: Introductionunclassified
“…Development of science is frequently related to scientific productivity, the ability to produce a scientific publication (Franceschet and Costantini, 2011). The publication can be measured through bibliometric indicators (Piro, F.N., 2011).…”
Section: Introductionmentioning
confidence: 99%